Venous Thromboembolism and High Grade Gliomas - Dhami, Mandeep S; Bona, Robert D; Calogero, John A; Hellman, Richard M (Thrombosis and Haemostasis, 1993)
A retrospective study was done to determine the incidence of and the risk factors predisposing to clinical venous thromboembolism (VTE) in patients treated for high grade gliomas. Medical records of 68 consecutive patients diagnosed and treated at Saint Francis Hospital and Medical Center from January 1986 to June 1991 were reviewed. The follow up was to time of death or at least 6 months (up to December 1991). All clinically suspected episodes of VTE were confirmed by objective tests. Sixteen episodes of VTE were detected in 13 patients for an overall episode rate of 23.5%. Administration of chemotherapy (p = 0.027, two tailed Fisher exact test) and presence of paresis (p = 0.031, two tailed Fisher exact test) were statistically significant risk factors for the development of VTE. Thrombotic events were more likely to occur in the paretic limb and this difference was statistically significant (p = 0.00049, chi square test, with Yates correction). No major bleeding complications were seen in the nine episodes treated with long term anticoagulation.We conclude that venous thromboembolic complications are frequently encountered in patients being treated for high grade gliomas and the presence of paresis and the administration of chemotherapy increases the risk of such complications.